Pathogenecity of two strains of rice yellow mottle virus on aromatic rice cultivars - Kanyeka, Z. L. (Tanzania Journal of Science, 2021)
Development of rice cultivars with resistance to rice yellow mottle virus (RYMV) requires characterization of pathogenecity of existing strains against susceptible cultivars. The pathogenecity of two RYMV strains; S4 and S“New” identified in Tanzania were assessed against seven local and introduced rice genotypes including cultivars Zambia, ITA173 and TXD 88. The two virus strains showed similar effects on the rice cultivar Zambia killing all the plants at 25d after inoculation. The strains significantly reduced the plant height, panicle length, and number of tillers per pot and total dry matter of all the two cultivars. In another trial, the pathogenecity of the two strains was assessed against four aromatic rice cultivars M-69-9, Loya, Shingo ya mwali and Motisoro. The analysis of variance revealed significant differences only among cultivars for all plant parameters except for the disease severity, which showed significant statistical differences for cultivars, strains and their interactions. The strain S“New” caused more severe disease incidences on inoculated plants than S-4 strain indicating its appropriateness to use in screening for RYMV resistance due to its aggressiveness on susceptible rice genotypes.